The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1177/0014402916664070
|View full text |Cite
|
Sign up to set email alerts
|

Writing Characteristics of Students With Learning Disabilities and Typically Achieving Peers

Abstract: There is a general consensus that writing is a challenging task for students with learning disabilities (LD). To identify more precisely the extent and depth of the challenges that these students experience with writing, the authors conducted a meta-analysis comparing the writing performance of students with LD to their typically achieving peers. From 53 studies that yielded 138 effect sizes, the authors calculated average weighted effect sizes, showing that students with LD obtained lower scores than their pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
117
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 136 publications
(136 citation statements)
references
References 57 publications
4
117
0
3
Order By: Relevance
“…Moreover, while students with disabilities scored lower on the norm‐referenced writing measure than peers without disabilities, the former scored just slightly below the mean on this assessment. This was unexpected, as students with disabilities typically experience considerable difficulty with writing (Graham et al, ). Consequently, additional research is needed to validate that writing attitudes and self‐efficacy account for unique variance in writing performance for students with disabilities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, while students with disabilities scored lower on the norm‐referenced writing measure than peers without disabilities, the former scored just slightly below the mean on this assessment. This was unexpected, as students with disabilities typically experience considerable difficulty with writing (Graham et al, ). Consequently, additional research is needed to validate that writing attitudes and self‐efficacy account for unique variance in writing performance for students with disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…These variables included poverty as represented by whether students did or did not receive free/reduced lunch, student's first language (English or another language) and disability status (students were identified as disabled or not). All three of these factors are related to how well students' write (Lee, ; e.g., Graham, Collins, & Rigby‐Wills, ; Mavrogenes & Bezruczko, ). Controlling for gender, free/reduced lunch status, first language, disability status and reading motivational beliefs allowed us to conduct a stringent test of whether writing motivational beliefs predict writing performance.…”
Section: The Current Studymentioning
confidence: 99%
“…Background knowledge, memory, and executive functions impact the writing of students with LD [71]. Graham, Collins, and Rigby-Wills [72] conducted a meta-analysis of 53 studies, comparing the writing of students with LD and peers without disabilities. In addition to needing support with all phases of writing, they found that writing "required the orchestration of handwriting, typing, spelling, and sentence construction skills" (Writing characteristics, p. 199) combined with the role of motivation.…”
Section: Writingmentioning
confidence: 99%
“…Students with learning disabilities (LD) tend to have a large number of writing deficits compared to their peers (Graham, Collins, & Rigby‐Wills, ; Koutsoftas & Gray, ; Lane & Lewandowski, ; Newcomer & Barenbaum, ; Poplin, Gray, Larsen, Banikowski, & Mehring, ; Troia, ), and these deficits maintain across the grades (Dockrell, Lindsay, Connelly, & Mackie, ; Poplin et al., ) unless these students receive intensive and special instruction (Schumaker & Deshler, ). Indeed, without such instruction, these students do not make appreciable gains in writing over time (Troia, Lin, Monroe, & Cohen, ), and they continue to write at the fourth‐grade level throughout their high‐school years (Warner, Schumaker, Alley, & Deshler, ).…”
mentioning
confidence: 99%